That Obscure Object of (Philosophical) Desire - Olmos, Paula (Informal Logic)

(untitled) (Informal Logic, 2023)
This paper is a response to H. Siegel’s “Arguing with Arguments” from a rhetorical perspective on argumentation. First I address Siegel’s concept of ‘argument in its abstract propositional sense’ and attempt to show that it is not at all an obvious object that should unquestionably be the privileged focus of argumentation theory. I then defend C. W. Tindale’s rhetorical perspective on argumentation against some of Siegel’s misreadings and also some of his legitimate disagreements regarding the relations between persuasion and rational justification and the way we should understand the source of argumentative normativity.